2013
DOI: 10.1111/bjh.12440
|View full text |Cite
|
Sign up to set email alerts
|

LITAF, a BCL6 target gene, regulates autophagy in mature B‐cell lymphomas

Abstract: Summary We have previously reported that LITAF is silenced by promoter hypermethylation in germinal center-derived B-cell lymphomas, but beyond these data the regulation and function of LITAF in B cells are unknown. Gene expression and immunohistochemical studies revealed that LITAF and BCL6 show opposite expression in tonsil B-cell subpopulations and B-cell lymphomas, suggesting that BCL6 may regulate LITAF expression. Accordingly, BCL6 silencing increased LITAF expression, and chromatin immunoprecipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…A recent study for the first time has demonstrated that LITAF , a novel target of BCL6, regulates autophagy in mature B-cell lymphomas [14]. This study provided evidences for the transcriptional repression of LITAF by BCL6 in B cells.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A recent study for the first time has demonstrated that LITAF , a novel target of BCL6, regulates autophagy in mature B-cell lymphomas [14]. This study provided evidences for the transcriptional repression of LITAF by BCL6 in B cells.…”
Section: Resultssupporting
confidence: 53%
“…Recent studies have showed, both mRNA and protein expression of LITAF are significantly down-regulated in germinal centre (GC) B-cell-like diffuse large B-cell lymphoma (GCB-DLBCL), which display constitutively high BCL6 expression [1113]. Interestingly, it has been demonstrated that LITAF is a novel target of BCL6 [14], providing new insights into the crosstalk between BCL6 and LITAF. In fact, BCL6 is a transcriptional repressor of the POZ/BTB zinc-finger protein family, acting as a key regulator for development of the germinal center (GC) and further differentiation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BCL6 is involved in the development of CD4+ T-follicular helper cells that play a critical role during the generation of germinal centers (Yu et al, 2009; Hollister et al, 2013). Thus, most B cell lymphomas arise from GC B cells need continued expression of BCL6 to maintain their survival (Hatzi et al, 2013; Bertolo et al, 2013). Targeted inhibition of these BCL6 functions has emerged as the basis for the rational design of lymphoma therapies and combinatorial regimens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to peripheral neuropathy, dysregulation of SIMPLE is also associated with arrhythmias and sudden cardiac death in patients with idiopathic prolonged QT interval duration (LQT syndrome) (70,71). SIMPLE also contributes to tumorigenesis (72)(73)(74), in which inflammatory pathways such as those utilized by IL-1 and TGF-␤ are frequently altered.…”
Section: T115n/t115nmentioning
confidence: 99%